586 views
5 votes
Can someone help with this please????

Can someone help with this please????-example-1

1 Answer

6 votes

Given:

The given function is:


f(x)=11x-11

To find:

The value of
(f\circ f^(-1))(-11).

Solution:

We have,


f(x)=11x-11

First we have to find the inverse of this function.

Putting f(x)=y, we get


y=11x-11

Interchange x and y.


x=11y-11

Isolate the variable y.


x+11=11y


(x+11)/(11)=y


y=(x+11)/(11)

Putting
y=f^(-1)(x), we get


f^(-1)(x)=(x+11)/(11)

Now,


(f\circ f^(-1))(-11)=f(f^(-1)(-11))


(f\circ f^(-1))(-11)=f\left((-11+11)/(11)\right)
\left[\because f^(-1)(x)=(x+11)/(11)\right]


(f\circ f^(-1))(-11)=f\left((0)/(11)\right)


(f\circ f^(-1))(-11)=f\left(0\right)

The given function is
f(x)=11x-11.


(f\circ f^(-1))(-11)=11(0)-11


(f\circ f^(-1))(-11)=-11

Therefore, the value of
(f\circ f^(-1))(-11) is
-11. Hence the correct option is A.

User RobertF
by
4.9k points